PENGEMBANGAN KURIKULUM PADA ASPEK ILMU PENGETAHUAN DAN TEKNOLOGI YANG BERBASIS LINGKUNGAN HIDUP MELALUI PENDEKATAN SAINTIFIK DI SEKOLAH DASAR - Dheni Redhiana (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2014)
Curriculum basically refers to the aim of national education which is to smarten the national life. Therefore, in developing the curriculum, it should focus on the nation intelligence aspect. Intelligent means not only some one owning the intellectuality but also with some skill as well as willingness and ability to utilize the intelligence to solve many problems in their social life. The curriculum development should consider the principles of developing the curriculum which will be the pillars or rules as the soul of the curriculum itself. The curriculum and learning in Elementary School should be able to change the students’ character and behavior into the better ones and to filter many negative impacts on knowledge and technology development happened in the real world. Beside, the curriculum also should be able to make the students master, utilize, and develop the science and technology and make them as the students learning media to improve their competence to achieve the national education purposes